(untitled) (Journal of Physical Education (Maringá), 2024)
The aim of the study was to verify the effect of eight weeks of creatine supplementation on cognitive function in patients with symptomatic peripheral arterial disease (PAD). Twenty-nine patients, of both sexes, were randomized (1:1) in a double-blind manner for administration of Placebo (PLA, n = 15) or creatine monohydrate (Cr, n = 14). The supplementation protocol consisted of 20g/day for one week, divided into four equal doses (loading phase), followed by single daily doses of 5g in the subsequent seven weeks (maintenance phase). Cognitive function was assessed using the Stoop test. The number of correct answers and response time (seconds) were considered. The evaluation was carried out before and after eight weeks of supplementation. The Generalized Estimation Equation Model was used for comparisons between groups. The level of significance was P <0.05. No significant differences were found for the number of correct answers (PLA: pre 26 ± 5 vs. post 26 ± 5; Cr: pre 24 ± 5 vs. post 25 ± 5, p = 0.801) or response time (PLA: pre 4.9 ± 6.1 s vs. post 4.9 ± 5.2 s; Cr: pre 2.7 ± 4.4 s vs. post 1.2 ± 4.6 s, p = 0.820). Eight weeks of creatine supplementation did not improve cognitive function in patients with symptomatic peripheral artery disease.